PENGARUH KESADARAN WAJIB PAJAK, SOSIALISASI PERPAJAKAN DAN PEMADANAN NIK SEBAGAI NPWP TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA SINGARAJA - Hermaswari, Diah Laksmi; Astawa, I Gede Putu Banu; Nyoman Ayu Wulan Trisna Dewi (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to analyze the influence of Taxpayer Awareness, Tax Socialization and Matching NIK as NPWP on Individual Taxpayer Compliance at the Singaraja Pratama Tax Service Office. This type of research uses a quantitative approach with a survey method through a questionnaire with 100 respondents. Data analysis was carried out using multiple linear regression with SPSS 26. The results of this study indicate that (1) taxpayer awareness has a positive effect on individual taxpayer compliance, (2) tax socialization has a positive effect on individual taxpayer compliance and (3) matching NIK as NPWP has a positive effect on individual taxpayer compliance.